2004
DOI: 10.1002/bjs.4469
|View full text |Cite
|
Sign up to set email alerts
|

Randomized clinical trial of the costs of open and laparoscopic surgery for colonic cancer

Abstract: Within 12 weeks of surgery for colonic cancer, there was no difference in total costs to society incurred by LCR and OCR. The LCR procedure, however, was more costly to the healthcare system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
132
0
8

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(147 citation statements)
references
References 18 publications
7
132
0
8
Order By: Relevance
“…The laparoscopic procedure was more expensive in terms of theatre costs, whilst the other hospital costs such as ward, ICU and HDU and complications were higher in the patients randomised to the open procedure. The results of this trial are consistent with other costing studies of laparoscopic surgery for colorectal cancer (Philipson et al, 1997, Khalili et al, 1998, Delaney et al, 2003, Janson et al, 2004. Khalili et al (1998) found similar costs between treatment groups, though the operating theatre costs were higher for laparoscopic surgery.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The laparoscopic procedure was more expensive in terms of theatre costs, whilst the other hospital costs such as ward, ICU and HDU and complications were higher in the patients randomised to the open procedure. The results of this trial are consistent with other costing studies of laparoscopic surgery for colorectal cancer (Philipson et al, 1997, Khalili et al, 1998, Delaney et al, 2003, Janson et al, 2004. Khalili et al (1998) found similar costs between treatment groups, though the operating theatre costs were higher for laparoscopic surgery.…”
Section: Discussionsupporting
confidence: 87%
“…The recent COLOR trial has provided a similar approach to the analysis of short-term costs undertaken in the current trial, with a sample of 210 Swedish patients from a multinational trial of 1200 patients with colon cancer (Janson et al, 2004). Societal costs were higher in the patients who underwent conventional open surgery, although as expected operative costs were higher in patients who underwent laparoscopic surgery.…”
Section: Discussionmentioning
confidence: 86%
“…The primary goal of the colon carcinoma laparoscopic or open resection (COLOR) trial was to compare 3-year cancer-free survival after laparoscopic and open resection for right colon, left colon, or sigmoid cancer, and the sample size was calculated accordingly. Laparoscopic colon resection for colonic cancer results in a smoother immediate postoperative period for the patient and improved health-related quality of life for 2-4 weeks compared with open surgery, at a higher cost for the first 3 months after surgery for hospitals but not in the societal perspective [14,18,19,23,24]. In the longer perspective, there was improved [16] or unchanged survival [17,21,22].…”
mentioning
confidence: 99%
“…A recent randomized study from Sweden has compared laparoscopic with open surgery for colonic cancer and concluded that within 12 weeks of surgery, there was no significant difference in total costs to society [18].…”
Section: Discussionmentioning
confidence: 99%